ChemInform Abstract: Na2Ti6O13: A Potential Anode for Grid‐Storage Sodium‐Ion Batteries. Issue 43 (7th October 2013) - Rudola, Ashish; Saravanan, Kuppan; Devaraj, Sappani; Gong, Hao; Balaya, Palani
Abstract Nanorods of the title compound are synthesized from a mixture of Na(OAc), Ti(O‐iPr)4, and hexadecyl‐trimethyl‐ammonium bromide in H2O and EtOH, followed by sintering of the obtained powder in air at 800 °C for 6 h.